Production of L-Lactic Acid by Thermotorelant Lactic Acid Bacteria - Nitaya Boontim (Science Faculty of Chiang Mai University, 2019)
L-Lactic acid has high commercial value since it is commonly used in food, pharmaceutical and chemical industries. It has recently received much attention for its use in biodegradable plastic production. The acid is industrially produced by either chemical synthesis or microbial fermentation. However, chemical synthesis is can only be achieved by the racemic mixture of the L(+) and D(-)-lactic acid. Thus, the objective of this study is to screen and select effective thermo-tolerant lactic acid bacteria for use in L-lactic acid production. A total of 111 lactic acid bacteria were isolated from various sources on deMan Rogosa and Sharp (MRS) agar. All of bacteria were tested on homo-fermentative/hetero-fermentative differential (HHD) medium, and the result showed that 104 isolates were homo-fermentative lactic acid bacteria. L-lactic acid and D-lactic acid production were determined by enzymatic method. The result indicated that the highest optical purity of L-lactic acid was produced from Lactobacillus salivarius L105. The highest L-acid production under optimum conditions was 10g/l with 98.7% optical purity when bacterial cultivation occurred in MRS medium containing 2% glucose, 2% beef extract, and pH 6.5 at 37°C for 24 hours.